Identification of human errors during device-related accident investigations. - Shepherd, M. (IEEE Engineering in medicine and biology magazine)
A minisystem is the smallest system that can deliver a single clinical benefit. Healthcare is delivered to patients through an assemblage of minisystems. It is the failure of these minisystems that reportedly results in between 44,000 and 98,000 iatrogenic deaths in the United States annually. Accident investigations are intended to identify the latent defects within these minisystems and to recommend corrective actions that will prevent a recurrence. Since human error is involved in approximately 69% of these deaths, understanding the fundamental causes of human error is important to an effective investigation. Device-related accident investigations require a three-step process to identify the deficiencies: 1) gathering clinical and engineering data surrounding an event, 2) analyzing the data to identify the components of the minisystem that contributed to the event, and, when operator error is identified, 3) translate the clinical actions of the operator to human error concepts. A case study of an incident involving a defibrillator which illustrates the process and recommendations for adjusting the minisystem to increase compatibility with the device operator are presented.